BILATERAL PARAMEDIAN THALAMIC AND MIDBRAIN INFARCTION: A Case Report - Andaka, D.; Nuartha, and A. A. B. N. (BALI MEDICAL JOURNAL, 2013)
Background: Bilateral paramedian thalamic and midbrain infarct is rare and present with varying symptoms. The occlusion of a rare arterial variant called the artery of Percheron results in bilateral thalamic infarcts, with or without midbrain involvement. To this date, the diagnosis of ischemic infarction due to occlusion of the artery of Percheronhas was uncommon. Case: We reports a 50 year-old man with acute ischemic infarcts of both paramedian thalami and midbrain, presenting with complete ophthalmoplegia, arreactive mydriasis pupils, and altered mental status (somnolent and fluctuating hypersomnia).Conclusions: Based on clinical and neuroimaging findings, we concluded this case as acute ischemic infarctions due to occlusion of the artery of Percheron.